Fonte de corrente alternada programável para ensaios de equipamentos elétricos - Marcus Correa de Morais (2006)
This work presents the project, implementation and construction of a programmable A.C. current source prototype featuring small power, large amplitude range and low total harmonic distortion for testing electrical energy meters. The work describes the system model, the choice of current ranges, the LC filter design, the topology and the digital control technique employed for closed-loop regulation of PWM inverter. To verify the proposed control scheme efficiency, an A.C. current source prototype was constructed. The results demonstrate that the DSP-based fully digital-controlled PWM inverter can achieve both good tracking responseand low total harmonic distortion. Finally, possible enhancements and future work perspectives are suggested.